Hiding in Plain Sight: Elopomorph Larvae Are Important Contributors to Fish Biodiversity in a Low-Latitude Oceanic Ecosystem - Moore, Jon A.; Fenolio, Dante B.; Cook, April B.; Sutton, Tracey T. (Frontiers in Marine Science, 2020)
Leptocephalus larvae of elopomorph fishes are a cryptic component of fish diversity in nearshore and oceanic habitats. However, identifying those leptocephali can be important in illuminating species richness in a region. Since the Deepwater Horizon oil spill in 2010, sampling of offshore fishes in the epi-, meso-, and upper bathypelagic depth strata of the northern Gulf of Mexico resulted in 8982 identifiable specimens of leptocephalus larvae or transforming juveniles, representing 90 recognized and established species and an additional 36 distinctive leptocephalus morphotypes not yet linked to a known described species. Leptocephali account for ~13% of the total species richness of fishes collected in the offshore region. A new morphotype of Muraenidae leptocephalus is described. DNA barcoding of selected specimens has further expanded the determination of several leptocephalus morphotypes.